Modeling, simulation and optimization of the rotating packed bed (RPB) absorber and stripper for MEA-based carbon capture. (5th December 2020) - Im, Dasom; Jung, Howoun; Lee, Jay H.
Highlights: Models of RPB absorber and stripper employing the MEA solvent are developed. Designs of the rotating packed bed units with MEA solvents of various wt% are suggested. The operating conditions of the MEA process with RPBs are optimized to minimize the total energy consumption. Abstract: Despite rising concern with climate change, carbon capture is yet to be implemented widely in the industry due to its size and cost. The rotating packed bed (RPB), a high gravity technology process, has been suggested to intensify the conventional packed bed. In this study, rigorous models of the RPB absorber and stripper for carbon capture are developed and implemented in the commercial simulator of gPROMS. The developed process models are validated with published steady-state experimental data and the entire carbon capture process comprising the RPB absorber, the RPB stripper, and other process units with solvent recycle is simulated. Initial designs of the rotating packed beds are suggested considering the flooding limit and capture rate. Then the steady-state optimal operation conditions minimizing the total energy of the MEA process with the intensified absorber and stripper are found and their behaviors are analyzed.